Diarrhea-Predominant Irritable Bowel Syndrome Is Associated With Diverticular Disease: A Population-Based Study - Jung, Hye-kyung (2009)
OBJECTIVES: A subset of patients with colonic diverticular disease have chronic gastrointestinal symptoms, and some have a clinical diagnosis of irritable bowel syndrome (IBS), but whether IBS and diverticular disease are linked is uncertain. We aimed to evaluate this association in the community. METHODS: A population-based, cross-sectional survey was conducted by mailing a valid symptom questionnaire to the eligible residents of Olmsted County, MN, aged 30 –95 years. Colonic diverticular disease (diverticulosis and diverticulitis) was ascertained through a review of the complete medical history of all responders. Subjects with at least one relevant test (colonoscopy, computed tomography (CT) scan, CT colonography, or barium enema) were included. IBS was defined using Rome II criteria. RESULTS: Among 2,267 eligible respondents, there were 1,712 subjects who had undergone colon testing (76%): 919 women (54%); mean (±s.d.) age 65 (±11 years). Colonic diverticular disease was identified in 44.4% (95% confidence interval (CI) 42.1–46.8) of the subject. IBS was reported by 8.8% (95% CI 6.9 –11.0) of men and 17.0% (95% CI 14.6 –19.6) of women. After adjusting for age and gender, the presence of IBS was associated with an increased odds for diverticulosis (odds ratio (OR) = 1.8, 95% CI 1.3 – 2.4) but not diverticulitis (OR = 1.7, 95% CI 0.9 –3.2). In those 65 years of age or older, the presence of IBS was associated with a ninefold higher odds for diverticulosis (OR = 9.4, 95% CI 5.8–15.1). Relative to the non-IBS subgroup, diarrhea-predominant IBS and mixed IBS were significantly associated with an increased odds for diverticular disease (OR = 1.9, 95% CI 1.1–3.2; OR = 2.6, 95% CI 1.0 –6.4, respectively). CONCLUSIONS: There is a significantly increased odds for colonic diverticulosis in subjects with IBS (relative to those without IBS). These results suggest that IBS and colonic diverticular disease may be connected.